Resisting the Opportunity for Change: How Congressional Campaign Insiders Viewed and Used the Web in 2016. (August 2018) - Druckman, James N.; Kifer, Martin J.; Parkin, Michael
This article explores congressional campaigning on the web in 2016. What impact did the unique nature of the 2016 election have on those involved with the creation and maintenance of congressional campaign websites? Did it cause them to alter their approach to online campaigning? Using data from a survey of campaign insiders, we find that the factors that influence how congressional campaigns view and use their websites were largely impervious to the unique electoral environment. Results show that, consistent with previous election years, campaigns maintained a fairly uniform view of likely visitors and target audiences, and they tended to see their campaign websites as digital hubs, best used for capturing the campaign's overall message. We also find that, as in other years, nonincumbents continued to use their websites to campaign more aggressively than incumbents. Overall, the results suggest that congressional campaigning on the web is primarily driven by stable factors that transcend technological advancements and shifts in the political environment.